Towards a Model of Describing Humour Translation: A Case Study of the Greek Subtitled Versions of Airplane! and Naked Gun - Asimakoulas, Dimitris (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractBeing rooted in a specific cultural and linguistic context, humour can pose significant problems to translation. This paper will discuss data collected from films in the light of a suggested framework based on script theory of humour initially proposed by Attardo and specifically adapted here for subtitling. The data include such categories as wordplay, where a more ‘semiotic’ approach is employed, comparisons, parody, disparagement and register humour. These data were culled from two films translated into Greek: Airplane! (1980), directed by David Zucker and Jim Abrahams and The Naked Gun: From the Files of the Police Squad (1988), directed by David Zucker, which exhibit a great concentration of verbal humorous sequences and inventive puns. It will be suggested that there was leeway to creatively solve linguistically/culturally based translation problems, although inconsistencies were to be observed.